1988
DOI: 10.1002/j.1460-2075.1988.tb02834.x
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione transferase activity and tissue distribution of a cloned Mr28K protective antigen of Schistosoma mansoni.

Abstract: A protective Mr28K antigen of Schistosoma mansoni, expressed from its cDNA, has been purified in a single step and shown to possess glutathione (GSH) transferase activity as predicted from sequence homologies with two mammalian GSH transferase multigene families. It is notable for its high 1‐chloro‐2,4‐dinitrobenzene GSH transferase and linoleic acid hydroperoxide GSH peroxidase activities. The major GSH transferase of S. mansoni has been purified and its subunit is identical to this Mr28K antigen by criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(71 citation statements)
references
References 28 publications
3
67
0
1
Order By: Relevance
“…Moreover, the mutation of Tyr at position 10 abrogated the PGDS activity of Sm28GST and its ability to impair LC migration, thus confirming the importance of this residue in the enzymatic activity of both mammalian and pathogen-derived PGDS. Altogether, along with its role in parasite survival strategies [34], Sm28GST is also a potent modulator of LC/DC migration during infection. Therefore, inhibition of the enzymatic (GST and PGDS) activities of Sm28GST by neutralizing Ab generated after immunization with the protein, may explain why this Ag is presently considered as an important vaccine candidate against schistosomiasis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mutation of Tyr at position 10 abrogated the PGDS activity of Sm28GST and its ability to impair LC migration, thus confirming the importance of this residue in the enzymatic activity of both mammalian and pathogen-derived PGDS. Altogether, along with its role in parasite survival strategies [34], Sm28GST is also a potent modulator of LC/DC migration during infection. Therefore, inhibition of the enzymatic (GST and PGDS) activities of Sm28GST by neutralizing Ab generated after immunization with the protein, may explain why this Ag is presently considered as an important vaccine candidate against schistosomiasis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GSTs have been identified and cloned from Schistosoma japonicum (27) and Schistosoma mansoni (28,29), trematode parasites of man. In the latter case, the enzyme is localized in the external tegument (29), and immunization of rats and mice with recombinant constructs results in a significant level of protection against challenge infection (28).…”
Section: Discussionmentioning
confidence: 99%
“…A 28kDa antigen (Balloul et al 1985), later identified as glutathione-S-transferase (Sm28GST; Taylor et al 1988) and fatty acid binding protein (Sm14; Moser et al 1991) emerged by this route.…”
Section: V) Immunogenicitymentioning
confidence: 99%